Mathematical Modeling of Terry Tissues Based on Physical and Mechanical Indicators (Texas Journal of Engineering and Technology, 2022)
This article involves building a mathematical model using a statistical analysis method based on the results of experimental analysis of capillary properties in the fields of air conductivity, water absorption and drying, tandem and archetypal threads from basic physical properties. Experiments from multi-factor planning in mathematical modeling of the physical properties of Terry's objects have resulted in the use of a method of determining the regression model, and the model created has been used to analyze the effects of hairy objects on physical properties for changes in hair length and fiber size.